Termodynamická stabilita ettringitu - Křižanová, Lucie (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Tato práce se zabývá termodynamickou stabilitou ettringitu, který vznikl hydratací yeelimitového slínku v soustavě s alitem. Stabilita byla sledována v laboratorním prostředí a v prostředí nasycené vodní páry za nízké a zvýšené teploty.

This thesis deals with the thermodynamic stability of ettringite, which is produced during hydration of yeelimite clinker with alite in the system. The stability was studied in a laboratory environment and in a saturated water steam at low and elevated temperatures.
Thermodynamic Stability of Ettringite
Keywords: Portlandský cement; ettringit; yeelimit; Portland cement; ettringite; yeelimite